Inovasi Desa Sruwen: Mengolah Limbah Minyak Jelantah Menjadi Lilin Aromaterapi Bernilai Ekonomi dan Ramah Lingkungan - Moh. Fadhlan Adzaky; Moh. Wildan; Ummi Nur Laila S (Jurnal Kabar Masyarakat, 2025)
Education is very important for the progress of a civilization and of course education is not only an academic activity, but also as a foundation for students to contribute and actively participate in society through service. Service itself is an activity carried out by individuals or groups, such as students, lecturers, or educational institutions, to make a positive contribution to society. In accordance with the mission of UNNES college which is dedicated to contributing to society, we UNNES students strive to solve problems in society. We collaborate with partners, namely Sruwen Village, to solve problems in used cooking oil waste so that it does not become useless waste and has an impact on health and the environment. Used Cooking Oil is one of the wastes that is very often found in households. Used cooking oil is the remaining used cooking oil produced from household activities, restaurants, or the food industry. So that UNNES KKN GIAT 11 students develop used cooking oil products that can be developed especially in Sruwen Village, namely aromatherapy candle products through education and training so that they can be applied directly by housewives in dealing with used cooking oil waste. This activity was carried out on February 27, 2025 and at 9 am. The target of this activity is the mothers of the PKK Induk Sruwen Village. Community service aims to provide readers with knowledge related to the processing of used cooking oil waste, providing solutions in solving used cooking oil waste in the community.